Marginal bone loss and soft tissue health around two-implant mandibular overdenture retained with milled versus selective laser melted cobalt chromium bar: a randomized clinical trial - Iman Adel El-Asfahani; Reem Abd El-Moatty; Gehan Fekry Mohamed; Hussein Abdelhady Hussein (BMC, 2024)
Abstract Background To assess marginal bone loss and soft tissue health around two-implant mandibular overdenture retained with milled versus selective laser-melted cobalt chromium (Co-Cr) bars. Method This research was set to be a parallel, triple-blinded, randomised controlled trial. Twenty completely edentulous patients received new conventional complete dentures according to conventional techniques. Two implants were placed at mandibular canine areas bilaterally, and patients were randomly allocated into two equal groups: the milled Co-Cr bar group and the selective laser melted (SLM) Co-Cr bar group. Marginal bone loss (MBL), modified plaque index (mPI), modified gingival index (mGI), and probing depth (PD) were evaluated at 0-month (baseline), 6-month, and 12-month follow-up visits. Repeated measures ANOVA test and Bonferroni's post-hoc test were used for parametric data as PD, while for non-parametric data as MBL, mGI, and mPI, Mann-Whitney U test and Friedman's test were used. A P-value ≤ 0.05 was set as the statistical level of significance. The study protocol was approved by the Faculty Research Ethics Committee at Minia University (636 4/10/2022). Registration for the clinical trial was made retrospectively on clinicaltrials.gov with ID NCT06401200 at 04/30/2024. Results The follow-up period (one year) was completed without a dropout. Regarding MBL, no statistically significant difference was found between the two groups throughout the study. However, the milled group showed significantly increased MBL from 0- to 6-month follow up period. In both groups, mPI increased significantly from 0- to 6-months post-loading. On the other hand, no statistically significant difference between the two groups was found regarding mPI and mGI throughout the study follow-up periods. The PD was significantly lower in the milled compared to the SLM group at the 6- and 12-month follow up period. Conclusion Two-implant mandibular overdenture retained with milled or SLM Co-Cr bar can provide an acceptable treatment option for completely edentulous patients regarding marginal bone loss and soft tissue outcomes.